Self-motion perception from expanding and contracting optical flows overlapped with binocular disparity - Ito, Hiroyuki; Shibata, Ikuko (Vision research (Oxford), 2005)
Expanding and contracting patterns were presented on different disparity planes to investigate the role of stereo depth in vection. Experiment 1 tested the effect of stereo depth on inducing vection with expanding and contracting flows on different disparity planes. Subjects reported whether they felt forward or backward self-motion. The results clearly showed the dominance of the background flow in determining one’s self-motion direction. Experiment 2 tested the effect of stereo depth on a vection direction using two expanding flows. The center of each expansion was displaced to either horizontal side. The subjects judged in which direction they were going when they felt vection. The results demonstrated that the subjects felt their heading biased toward the direction of the center of the farther expansion while feeling vection. The heading perception from the expanding flow was determined only by the background flow, not by 2-D integration of the retinal motion. The result demonstrates the importance of background flow produced by stereo depth in determining one’s self-motion from an expanding/contracting motion.